IDENTIFIKASI KESALAHAN DALAM MENYELESAIKAN SOAL ARITMATIKA SOSIAL SISWA KELAS VIII SMP NEGERI 4 PAREPARE - Rahma Rahma (Tautologi: Journal of Mathematics Education, 2025)
This qualitative descriptive study aimed to identify errors in solving social arithmetic problems among eighth-grade students at the UPTD of SMP Negeri 4 Parepare. The subjects were eighth-grade students, specifically class VIII.2. Two students were selected for in-depth identification of errors they experienced in solving social arithmetic problems. Data collection techniques used test administration and interviews. Students were given tests consisting of social arithmetic problems. Before being used, the questions were tested for validity. After obtaining the research data, the researchers analyzed the data using triangulation. The data analysis technique consisted of data reduction, data presentation, and data verification. The results of this study indicate that errors experienced by students in solving social arithmetic problems include conceptual errors and principle errors. The contributing factors include a lack of interest in learning mathematics, which leads to students being less thorough in their work on the problems, as well as internal factors and a lack of understanding of the material's concepts and prerequisites.